MoS2/Polymer Heterostructures Enabling Stable Resistive Switching and Multistate Randomness. Issue 42 (26th August 2020) - Chai, Jianwei; Tong, Shiwun; Li, Changjian; Manzano, Carlos; Li, Bing; Liu, Yanpeng; Lin, Ming; Wong, Laimun; Cheng, Jianwei; Wu, Jing; Lau, Aaron; Xie, Qidong; et al.
Abstract: Resistive random‐access memories (ReRAMs) based on transition metal dichalcogenide layers are promising physical sources for random number generation (RNG). However, most ReRAM devices undergo performance degradation from cycle to cycle, which makes preserving a normal probability distribution during operation a challenging task. Here, ReRAM devices with excellent stability are reported by using a MoS2 /polymer heterostructure as active layer. The stability enhancement manifests in outstanding cumulative probabilities for both high‐ and low‐resistivity states of the memory cells. Moreover, the intrinsic values of the high‐resistivity state are found to be an excellent source of randomness as suggested by a Chi‐square test. It is demonstrated that one of these cells alone can generate ten distinct random states, in contrast to the four conventional binary cells that would be required for an equivalent number of states. This work unravels a scalable interface engineering process for the production of high‐performance ReRAM devices, and sheds light on their promising application as reliable RNGs for enhanced cybersecurity in the big data era. Abstract : MoS2 /polymer‐heterostructure‐based resistive switching devices are demonstrated. These devices show much improved switching performance, such as low set/reset voltage, high on/off ratio, and device stability during cycle to cycle operation, and thus enable potential applications in random number generation for enhanced cybersecurity.